Contexto nacional e internacional y necesidades de la formación posgradual en baja visión (2021)
An individual with Low Vision is one who has limited vision and even after his best optical prescription, he presents visual acuity alteration ranging from (20/60) to light perception or a field of view of 20 degrees from the point of fixation, but uses his visual system for planning and carrying out an activity